The repressor MDBP-2 is a member of the histone H1 family that binds preferentially in vitro and in vivo to methylated nonspecific DNA sequences. - Jost, J P (1992)
MDBP-2 is a repressor that binds preferentially to methylated DNA. Peptides derived from MDBP-2 were sequenced. The sequences of the two peptides, KPAGPS-VTELITK and ALAAGGYDVEK, are identical to those found in the chicken histone H1 core protein. In SDS/polyacrylamide gels MDBP-2 has an apparent molecular mass of 21 kDa, and antibodies directed against calf thymus total histone H1 cross-react with MDBP-2. The preferential binding of affinity-purified MDBP-2 to methylated DNA is not sequence-specific but requires a minimum length of 30 base pairs and one pair of symmetrically methylated (i.e., methylated on both strands) CpG dinucleotides. As previously shown, there is a decrease in the binding activity of MDBP-2 to methylated DNA upon estradiol treatment. Immunoblots show that upon estradiol treatment the amount of immunocrossreacting MDBP-2 protein remains unchanged. MDBP-2 enables another protein to bind DNA which by itself does not bind methylated DNA. Ultraviolet crosslinking and selective immunoadsorption assays with anti-histone H1 antibodies show that in vivo MDBP-2 preferentially binds to the methylated repressed vitellogenin gene. It is concluded that MDBP-2 may participate in the long-term silencing of genes (formation of heterochromatin) through selective binding to methylated DNA.